Empowering Students in Transition - Sullivan, Ann-Catherine (Frontiers in Public Health, 2016)
The purpose of this study was to (a) identify potential benefits for students with disabilities taking part in a physical activity program with same-age typical peers on a Midwest university campus and (b) to determine if the program impacted the students with disabilities empowerment. Empowerment theory was used to determine how transition students’ attitudes change over the course of the semester while participating in a workout buddy program with same-age college peers. The program was structured to provide a sense of empowerment to students to make their own decisions and learn for themselves so they do not feel a lack of power in their lives. This study implemented elements of a quantitative design but a majority utilized a qualitative design based on the assumptions of the Interpretivist paradigm. The quantitative design elements focused on the analysis of two questionnaires: Sports Questionnaire and the Perceived Control Scale Questionnaire. The analysis of the focus group data revealed the following themes as positive effects of the intervention: positive effect on empowerment, how happy the program made the students, what benefits the students gained from the program, the student’s familiarity with university students, and the environment, and, lastly, the students ability to ask for assistance when need. Findings from the study determined that the empowerment of the students with disabilities was impacted while participating in the program. In general, the findings of gaining empowerment were similar to previous studies in that students with disabilities are able to gain empowerment from participation in fitness and recreation programs. The researcher noted during focus groups that some of the Best of Both Worlds (BOBW) students were not confident in starting conversations with their university peers. Although the BOBW students felt a sense of losing empowerment with this specific instance, there was an overall positive impact on the BOBW students’ empowerment. By giving the students the opportunity to participate and socialize with peers of their own age at a college setting, they were able to gain a sense of empowerment in their own life.